Svecofennian granitic magmatism in the Salo area, SW Finland − in situ U−Pb age determinations on zircon and monazite - Penttinen, Heidi (My University, 2019)
The bedrock of southern Finland was formed in a series of collisional events during the Svecofennian orogeny c. 1.92−1.79 Ga ago. The orogeny is divided in two main compressional stages: the Fennian (1.89−1.87 Ga) and Svecobaltic (1.84−1.79 Ga) orogenies. The Fennian stage resulted in synorogenic mafic to felsic magmatism, which in southern Finland was overprinted by Svecobaltic late-orogenic granites accompanied with high-temperature, lowpressure metamorphism and crustal melting. The compressional stages were intervened by an intra-orogenic stage (1.86−1.84 Ga) defined by bimodal magmatism in an extensional tectonic regime. The aim of this study was to determine the age of Svecofennian felsic magmatism, metamorphic events and deformation in the Salo area, SW Finland. The bedrock of the Salo area is characterised by Svecofennian granitoids, anatectic granites as well as migmatised metasedimentary and metavolcanic rocks, metamorphosed in higher amphibolite to granulite facies. The field work was focused along the Turku−Helsinki E18 highway running through the research area, between Paimio and Suomusjärvi. For the purpose of this study, 4 samples were collected for zircon and monazite separation. The U−Pb age determinations were performed on LA-SC-ICP-MS and LA-MC-ICP-MS equipment. Whole rock geochemical ICP-MS analysis and optical petrography were also applied for rock type classification. Based on the obtained results, a new type of 1.86−1.85 Ga felsic magmatism was discovered in the Salo area. The Hiittenmäki granite, with a granodioritic affinity, yielded a U−Pb concordia age of 1861±3 Ma from prismatic igneous zircons, whereas the prismatic zircons of the Hurtinmäki granite produced an upper intercept age of 1853±3 Ma. Both granites experienced metamorphic zircon recrystallisation and zircon growth at c. 1.83−1.82 Ga. The monazites of both samples yielded similar ages. The Hiittenmäki granite is the closest representative of the intra-orogenic magmatism yet discovered in the Salo area. The Kuturamäki leucosome evidenced a semi-continuous metamorphism and crustal anatexis between 1.84−1.81 Ga from anhedral zircons and grain rims. Episodic metamorphism of similar age was observed in the Hietamäki granite. An inherited population of 1.86 Ga was also recognised in the cores of both the Kuturamäki leucosome (zircons) and the Hietamäki granite (monazites). Products of the 1.86 Ga magmatism were thus among the sources of these partial melts. As detrital zircons were typical in all samples, the granitic melts were derived from partial melting of at least partly sedimentary sources. Age groups of 2.1−1.95 Ga and 1.93−1.87 Ga were abundant within zircons, as well as to some extent within monazites, reflecting the maximum age of the protoliths of partial melting. The oldest inherited zircon yielded an age of c. 3.1 Ga.

Etelä-Suomen kallioperä muodostui Svekofennisessä orogeniassa n. 1.92−1.79 Ga sitten, sarjassa kollisionaalisia tapahtumia. Orogenia voidaan jakaa kahteen kompressionaaliseen vaiheeseen: Fenniseen (1.89−1.87 Ga) ja Svekobalttiseen (1.84−1.79 Ga) orogeniaan. Fennisessä vaiheessa syntyi synorogenista, mafisesta felsiseen vaihtelevaa magmatismia, jonka peittivät korkean lämpötilan, matalan paineen metamorfoosin ja kuoren sulamisen myötä muodostuneet myöhäis-orogeeniset graniitit. Kompressionaalisten vaiheiden välissä vaikutti intra-orogeeninen vaihe (1.86−1.84 Ga), jolloin oli tyypillistä ekstensionaaliseen tektoniikkaan liittyvä bimodaalinen magmatismi. Tämän tutkimuksen tarkoituksena oli määrittää svekofennisen magmatismin ja metamofisten tapahtumien ikä Salon alueella, Lounais-Suomessa. Salon alueen kallioperälle tyypillisiä ovat svekofenniset granitoidit, anatektiset graniitit sekä migmatoituneet metasedimentti- ja metavulkaniittikivet, jotka ovat käyneet läpi korkean amfiboliitti- ja granuliittifasieksen metamorfoosin. Kenttätyöt keskittyivät tutkimusalueen läpi kulkevan Turku−Helsinki-moottoritien (E18) varrelle, Paimion ja Suomusjärven välille. Tutkimusta varten kerättiin neljä näytettä, joista separoitiin zirkoneita ja monatsiitteja. U−Pb ikämääritykset toteutettiin LA-SC-ICP-MS- ja LA-MC-ICP-MSlaitteistoilla. Lisäksi, ICP-MS-laitteistolla suoritettuja geokemiallisia kokokivianalyysejä sekä optista petrografiaa hyödynnettiin kivilajien luokittelussa. Saatujen tulosten perusteella uudenlainen 1.86−1.85 Ga -ikäinen felsinen magmatismi löydettiin Salon alueelta. Granodioriittimaisen Hiittenmäki-graniitin konkordiaiäksi saatiin 1861±3 Ma prismaattisista zirkoneista, kun taas Hurtinmäki-graniitin prismaattiset zirkonit antoivat yläleikkauspisteiäksi 1853±3 Ma. Molemmat graniitit kokivat metamorfista zirkonien uudelleenkiteytymistä ja zirkonien kasvua n. 1.83−1.82 Ga sitten. Näytteiden monatsiitit antoivat vastaavat iät. Hiittenmäki-graniitti on tähän mennessä lähin vastine intraorogeeniselle magmatismille Salon alueella. Kuturamäki-leukosomin vierasmuotoiset zirkonit ja rakeiden reuna-alueet paljastivat suhteellisen jatkuvan metamorfoosin ja kuoren sulamisen tapahtuneen 1.84 ja 1.81 Ga välisenä aikana. Samanikäinen jaksottainen metamorfoosi todettiin Hietamäki-graniitissa. Peritty 1.86 Ga -populaatio tunnistettiin rakeiden ytimistä sekä Kuturamäki-leukosomissa (zirkoneista) että Hietamäki-graniitissa (monatsiiteista). Niinpä näiden osittaissulien lähteisiin kuului 1.86 Ga -ikäisen magmatismin tuotteita. Koska detritaalisia zirkoneita löydettiin kaikista näytteistä, graniittiset sulat syntyivät ainakin osittain sedimenttikivien osittaissulamisen kautta. Ikäryhmät 2.1−1.95 Ga ja 1.93−1.87 Ga olivat vahvasti edustettuina zirkoneissa, sekä jossain määrin myös monatsiiteissa, heijastaen osittaissulamisen protoliittien maksimi-ikää. Vanhin periytynyt zirkoni oli iältään n. 3.1 Ga.
Keywords: Svecofennian orogeny, partial melting, U−Pb dating, LA-ICP-MS